A survey of pyritised animal, plant, and trace fossils and concretionary pyrites, Germav Formation, southeastern Turkey - Bölücek, C; Ilhan, B (Elsevier France-Editions Scientifiques Medicales Elsevier, 2006)
The sulphide-bearing rocks of the Upper Cretaceous Germav Formation in southeastern Turkey (Bozova-Urfa) and the morphologically varied sulphide occurrences they contain have been investigated. Pyrite and marcasite are the main sulphide minerals; lesser bravoite and millerite also Occur. Pyritised branches and leaves, trace fossils, and animal microfossils and macrofossils are abundant. Most of the concretionary and authigenic concretionary pyrite occurrences are probably related to burrows. The concretionary pyrites have low Co and high Ni contents and low Co:Ni ratios. The pyrite-rich lithostratigraphic sequences were deposited in a deep-sea environment, and pyrite mineralization developed in syn-sedimentary, early diagenetic and epigenetic stages under anoxic conditions.
Keywords: concretionary pyrite; Co : Ni ratio; southeastern Turkey; trace fossil